THE EFFECT OF EFFLEURAGE MASSAGE TO PAIN INTENSITY OF FIRST STAGE LABOR IN INPARTU MOTHERS AT LINEZ CLINIC OF GUNUNGSITOLI IN 2018 - Saragih, Hanna Sriyanti (Poltekkes Kemenkes Medan, 2019)
Pain in labor is a manifestation of the contraction (shortening) of the uterine muscle, and it was caused by stretching of the uterine and cervical segments as well as the presence of uterine muscle ischemia. According to WHO (World Health Organization) in 2015, it was estimated that every year 830 women died from complications of pregnancy and childbirth. One method that was very effective in dealing with pain is effleurage massage which was massage technique using the palms of the fingers with a circular motion pattern on the abdomen, waist or thighs. The purpose of this study was to determine the effect of effleurage massage on the intensity of first-stage labor pain in maternal mothers at Linez clinic of Gunungsitoli in 2018. This type of research was guasy Experiment research design with non equivalent control group design. In this design, the grouping of sample members in experimental group and the control group was not random, using wilcoxon test. The population in this study were mothers in first pregnancy as many as 52 people, with a total sample of 20 experimental groups and 20 control groups. The data used were primary data using observation sheets. From the research results, obtained p value 0.0001, it can be concluded that there was significant effect between experimental group and control group. It was hoped that midwives will update their midwifery service and practices such as participating in the latest midwifery training, so that they can increase their knowledge and apply it when conducting childbirth care as effort to reduce labor pain. Keywords: Effluerage Massage, Pain Intensity of First Stage Labor